Estimating Annual Forage Yields with Plant Available Water and Growing Season Precipitation - J. D. Holman; A. Obour; I. Kisekka; A. Schlegel; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2017)
Forage production is important for western Kansas region’s livestock and dairy industries and has become increasingly important as irrigation-well capacity declines. Forages require less water than grain crops and may allow for increased cropping intensity and opportunistic cropping. Being able to estimate forage production is important for determining forage availability versus forage needs. Data from several studies were used to quantify annual forage yield response to plant available water (PAW) at planting and growing season precipitation (GSP). In addition, water use efficiency was quantified. Forages evaluated included winter triticale, spring triticale, and forage sorghum.
Keywords: forage; yield; soil water; modelling; precipitation